EXPERIENCE OF TWO COSTA RICANS LIVING WITH HUMAN IMMUNODEFICIENCY VIRUS (HIV) AND THEIR CHALLENGES IN HEALTH ACCESS - Bosshard Monge, Nathalie (2025)
Human Immunodeficiency Virus (HIV) affects the immune system in a progressive way, causing Acquired Immunodeficiency Syndrome (AIDS) if viral replication is not effectively controlled. The main objective of this research was to know the life experiences of two people living with HIV, their perceptions about health care access and the disease’s impact on their lives, from a qualitative phenomenological perspective, by applying semi-structured interviews to two adult males, twenty-seven and thirty years old, respectively. It was found that both received acceptable treatment from health care workers. In addition, the VIH infection made a significant impact on several aspects of their lives, causing both negative and positive effects. Amongst conclusions, the life experience of these two people living with HIV is influenced by many factors, like those personal and structural in nature. They both present similar experiences regarding diagnosis and quality of health care services; however, perceptions related to the impact differ, since for patient 1 his family was an important factor to face the seropositive diagnosis, meanwhile, for patient 2 this was not part of his support system to rely on and deal with it.